Thiazolidinedione-Induced Fluid Retention: Recent Insights into the Molecular Mechanisms - Jerzy Bełtowski; Jolanta Rachańczyk; Mirosław Włodarczyk (PPAR Research)
Peroxisome proliferator-activated receptor-γ (PPARγ) agonists such as rosiglitazone and pioglitazone are used to improve insulin sensitivity in patients with diabetes mellitus. However, thiazolidinediones induce fluid retention, edema, and sometimes precipitate or exacerbate heart failure in a subset of patients. The mechanism through which thiazolidinediones induce fluid retention is controversial. Most studies suggest that this effect results from the increase in tubular sodium and water reabsorption in the kidney, but the role of specific nephron segments and sodium carriers involved is less clear. Some studies suggested that PPARγ agonist stimulates Na+ reabsorption in the collecting duct by activating epithelial Na+ channel (ENaC), either directly or through serum and glucocorticoid-regulated kinase-1 (SGK-1). However, other studies did not confirm this mechanism and even report the suppression of ENaC. Alternative mechanisms in the collecting duct include stimulation of non-ENaC sodium channel or inhibition of chloride secretion to the tubular lumen. In addition, thiazolidinediones may augment sodium reabsorption in the proximal tubule by stimulating the expression and activity of apical Na+/H+ exchanger-3 and basolateral Na+- cotransporter as well as of Na+,K+-ATPase. These effects are mediated by PPARγ-induced nongenomic transactivation of the epidermal growth factor receptor and downstream extracellular signal-regulated kinases (ERK).